Monetary theory: selected readings - Clower, Robert W. (Harmondsworth : Penguin, 1969)
This is a collection of scholars in economist on the subject matter of money, theories of money etc. This volume is intended to provide a representative sample of traditional and modern thinking about the role of money in economic activity.
includes index
Bibliography: p. 341-348.
usc 05/07/17
Loans
Keywords: Money